Parasites and plantations: Disease, environment and society in efforts to induce extinction of hookworm in Jamaica, 1919–1936 - Jonathan D. Roberts; Lorna L. Waddington; Rupert J. Quinnell; Graham Huggan; Alison M. Dunn (Cambridge Prisms: Extinction)
Studies of extinction typically focus on unintended losses of biodiversity and culture. This study, however, examines an attempt to induce extinction of a parasite: human hookworm (Necator americanus and Ancylostoma duodenale). Our interdisciplinary approach integrates medical history and epidemiology using records created by the Jamaica Hookworm Commission of 1919–1936. We show that the attempt to induce the extinction of hookworms was driven by its perceived effects on labour productivity and consequent status as an ideological and economic threat. We use spatial epidemiology to describe the relationships between parasites, environments and the working conditions of plantation labourers. Using data from 330 locations across Jamaica in which 169,380 individuals were tested for hookworm infection we show that the prevalence of hookworm infection was higher in districts surrounding plantations. Prevalence decreased with the temperature of the coldest month, increased with the amount of rainfall in the driest month, and increased with vegetation quantity (normalised difference vegetation index). Worm burden (and thus pathology) varied greatly between individuals, even those living together; hookworm infection varied between environments, socioeconomic conditions and individuals. Nevertheless, the conditions of labour shaped the distribution of hookworms. Plantations both spread and problematised hookworms, driving efforts to bring it to extinction.